Nonlinear network modeling of multi-module floating structures with arbitrary flexible connections. (November 2015) - Zhang, H.C.; Xu, D.L.; Xia, S.Y.; Lu, C.; Qi, E.R.; Tian, C.; Wu, Y.S.
Abstract: Multiple floating modules connected by flexible connectors can be viewed as a network structure. A standard modeling process for multi-module floating structures in arbitrary topology is presented by using network theory. A three-dimensional model is developed using the linear wave theory, dynamic model of single floating module, constitutive model of flexible connectors and model of a mooring system. As a typical application, a floating airport model is established and further its nonlinear dynamic responses and connector loads are analyzed. Numerical results show that the traditional linear analysis may underestimate the actual results. The methodology applied in this paper is extensible to many engineering problems with network structures alike. Highlights: Flexibly connected multi-module floating structure can be treated as a network. A 3D model for multi-module floating structures with arbitrary topology is developed. Nonlinearity may cause significant effect, should not be simplified by linearization. The network methodology can be applied to engineering problems with network alike.